2018
DOI: 10.1515/intag-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar on the unsaturated hydraulic conductivity of two amended soils

Abstract: Water and solute transports in the vadose zone depend on the distribution, size, shape and configuration of the pores. They affect the soil hydraulic properties and, consequently, the directly related processes such as water storage, infiltration, groundwater recharge, and also erosion and runoff. Soils amended with biochar are prompt to improve their physical and hydraulic properties. Biochar addition alters not only porosity, the water retention pattern and the derived pore distribution, but also the hydraul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Long-term application of heavy rates of manure may cause more unfavorable hydrological Flow through an unsaturated soil is complex and non-linear and is strongly dependent on the pore geometry, water content, and matric potential [61,62]. Studies reporting the effects of soil amendments on K unsat are very few [37,38]. According to Villagra-Mendoza [37], addition of BC enhances soil microporosity, hence enhancing K unsat at higher matric potentials and rapidly decreasing towards lower potentials of sandy and sandy loam soils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term application of heavy rates of manure may cause more unfavorable hydrological Flow through an unsaturated soil is complex and non-linear and is strongly dependent on the pore geometry, water content, and matric potential [61,62]. Studies reporting the effects of soil amendments on K unsat are very few [37,38]. According to Villagra-Mendoza [37], addition of BC enhances soil microporosity, hence enhancing K unsat at higher matric potentials and rapidly decreasing towards lower potentials of sandy and sandy loam soils.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reporting the effects of soil amendments on K unsat are very few [37,38]. According to Villagra-Mendoza [37], addition of BC enhances soil microporosity, hence enhancing K unsat at higher matric potentials and rapidly decreasing towards lower potentials of sandy and sandy loam soils. Another study found that long-term manure application had little or no effect on K unsat (−0.3, −0.5, −0.7, and −1.0 kPa) [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might assume a higher resistance of the biochar amendments to internal pore changes and to the formation of macro-aggregates during drying. As reported in Villagra-Mendoza and Horn [59], under initial infiltration conditions, when the soil is partially moistened, the higher the fraction of biochar, the higher is the transport of water (in terms of unsaturated hydraulic conductivity) due to the intensification of a finer inter-particle pore formation, especially in the sandy loam amendments. This could be another mechanism that may help to keep similar infiltration conditions along the WD cycles.…”
Section: Discussionmentioning
confidence: 56%
“…Owing to the high sensitivity to pore size distribution influenced by soil texture and management practices, SHC displays relatively high spatial variability 9,15,20,22,23 . Therefore, knowledge of the spatial distribution of SHC is essential in selection of the most appropriate localised management practices and amendments to improve water use efficiency in agriculture and to minimise the use and leaching of chemicals 24,25,26,27 . The spatial distribution of soil properties, including saturated hydraulic conductivity, can be assessed by classical and spatial statistics.…”
Section: Introductionmentioning
confidence: 99%